Evaluation of Botanical and Chemical Treatments an Growth and Productivity af Potato - Bohora, Anisha; Rai, Supana; Poudel, Pratikshya; Shah, Nitesh Kumar (Journal of Agriculture and Resource Management, 2024)
Potato (Solanum tuberosum L.) is one of the most significant Solanaceous vegetable crops throughout the world, and a food and cash crop in many parts of the world. A field experiment was carried out in Jorayal Rural Municipality- 2, Budar, Doti from late winter to early summer season. The objective of the study is to assess the impact of botanicals and chemicals on the growth and yield of potatoes in Budar- 02, Doti, Nepal, with an emphasis on the need for environmentally sustainable farming practices. Five treatment comprising chemical fungicides, botanicals and a bio-control agents i.e. Mancozeb, Syzygium cumini L.(Jamun), Allium sativum L (Garlic), Eupatorium adenophorum Spring (Banmara) were arranged in a randomized block design and replicated six times. The result showed that botanical treatments positively influenced plant growth. It indicated a consistent increase in plant height throughout the crop growth period, with Mancozeb and Banmara treatments exhibiting the highest heights i.e 35 and 34.33 cm respectively. Compared to control, yield was also increased by 36.16% in Mancozeb and 30% in Jamun respectively. These findings imply that botanicals holds immense potential as a non-toxic, environmentally friendly and at the same time sustainable alternative to chemicals, contributing to agricultural productivity and environmental preservation.